Keigo's Subtitle Translation Strategy in Gekijouban Violet Evergarden Movie - Ade Palupi Septyaningtyas; Wiwik Retno Handayani (International Journal Labs, 2025)
The development of the digital era has introduced new perspectives in audiovisual translation, particularly in subtitle translation for films. However, challenges such as linguistic factors and cultural differences between source and target languages persist, especially in translating Japanese keigo (polite language), which conveys respect and politeness. This study aims to analyze the strategies used in translating Japanese keigo subtitles into Indonesian in the film Gekijouban Violet Evergarden. Employing a qualitative-descriptive and contrastive research design, the study collected 317 subtitle data from the Netflix version of the film using the listen-note technique. The analysis was guided by Gottlieb’s (2021) theory of subtitle translation strategies. The findings revealed eight out of ten translation strategies, with paraphrase being the most dominant (41.33%), followed by transfer (36.91%). The prevalence of paraphrase highlights the complexity of Japanese keigo, which lacks direct equivalents in Indonesian, necessitating adjustments to maintain naturalness and nuance. Other strategies, such as expansion, condensation, and deletion, were also employed to address cultural and linguistic gaps. The study underscores the importance of translators’ interpretive skills in preserving the subtleties of keigo while ensuring audience comprehension. These findings contribute to the field of audiovisual translation, offering insights for translators working with politeness varieties in Japanese-Indonesian contexts. Further research is recommended to explore additional strategies and broader applications in multimedia translation.